Interpretation and meaning in philosophy and religion - Grube, Dirk-Martin. (Philosophy of History and Culture, 2016)
Interpretation and Meaning in Philosophy and Religion synthesizes cutting-edge philosophical reflections on interpretation with their application to religion. For this, new theoretical insights on interpretation by Krausz, Lamarque, Leddy, Hagberg, and Gibson are examined. Topics cover multiplism (i.e. interpretative pluralism), the goal of interpretation and its starting point. These concepts are then studied in relation to the practice of interpreting religious texts. For example, Grube proposes that the action-relevance of religious interpretations limits the possibility of tolerating divergent interpretations, Karrer-Grube challenges Lamarque's insistence on a firm starting point, and Gokhale challenges Krausz by arguing that Vedantic practices of interpretation are non-multiplist.